Alfred Loisy y las profecías mesiánicas en la apologética. Una discusión olvidada de la crisis modernista = Alfred Loisy and messianic prophecies in apologetics. A forgotten discussion of the modernist crisis - Switek, Mateusz (Scripta theologica, 2025)
A key figure in the modernist crisis, Alfred Loisy had a major influence on the debates on revelation, miracle and apologetics. However, his texts also include another theme that is much less discussed, namely that of the proof from prophecy. The paper introduces the context of this theological discussion and examines the evolution of Loisy’s thinking on messianic prophecy, from his defence of Catholic positions against rationalism, through his polemics on the proper form of apologetics, to skeptical positions. This will lead to ask whether the issues raised by Loisy remain relevant to contemporary theology.